(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The objective of this study was to investigated the effect of peer tutoring on reading comprehension of pupils with hearing impairment. The study was conducted in Enugu state, Nigeria using a pre-test post-test quasi experimental research design. The participants were 30 pupils with hearing impairment. Reading Comprehension Achievement Test (RCAT) was used for data collection in this study. The study had both experimental and control groups. The participants in the experimental group were taught using peer tutoring teaching strategy while the control group were taught with conventional teaching method. Two research questions and two hypotheses guided the study. Mean and standard deviation were used to answer the research questions while analysis of covariance (ANCOVA) was used to test the hypotheses at 0.05 level of significance. The findings of the study indicated that peer tutoring teaching strategy significantly improved reading comprehension of pupils with hearing impairments and that the interaction effect of teaching strategies and gender on pupils with hearing impairments reading comprehension was not significant. Based on the findings, the study discussed the implications, made some useful recommendations and suggestions for further studies.